Global, regional, and national burden of gastroesophageal reflux disease (1990–2021): age-period-cohort analysis and Bayesian projections - Liumei Mo; Zhenhao Liu; Wenjing Cao; Hanxian Gong; Jincheng Wu; Mingzhuo Lin; Wei Pan (Frontiers in Public Health, 2025)
BackgroundGastroesophageal reflux disease (GERD) is a common chronic upper gastrointestinal disorder that causes discomfort and increases the risk of esophageal adenocarcinoma. The global burden of GERD has steadily increased, establishing it as a critical public health issue. This study systematically evaluated the global, regional, and national burden of GERD from 1990 to 2021, revealing epidemiological trends and regional disparities to inform targeted intervention strategies.MethodsWe utilized data from the 2021 Global Burden of Disease Study (GBD) to assess the prevalence, incidence, and years lived with disability (YLDs) of GERD. Key indicators included age-standardized prevalence rate (ASPR), age-standardized incidence rate (ASIR), age-standardized YLDs rate (ASYR), and estimated annual percentage change (EAPC). Analyses were stratified by age, gender, and socio-demographic index (SDI). Age-period-cohort (APC) models were applied to examine trends in the 15–49 age group, and Bayesian APC models were used to project future trends.ResultsIn 2021, global GERD prevalence reached 825.6 million (95% uncertainty interval: 732.99–925.56 million). From 1990 to 2021, incident cases, prevalent cases, and YLDs rose by 83.16, 80.06, and 82.46%, respectively. The ASIR, ASPR, and ASYR all showed upward trends, with EAPCs of 0.097, 0.076, and 0.083. The highest burden of ASIR, ASPR, and ASYR was observed in Tropical Latin America in 2021, while the lowest was in East Asia. Regions with lower SDI had higher ASIR, ASPR, and ASYR. In the 15–49 age group, the GERD burden increased with age across all SDI regions, with unfavorable period effects observed in high and high-middle SDI regions, as well as adverse cohort effects in high-middle and middle SDI regions. Projections indicate that by 2035, global GERD cases in this age group will reach 527.2 million (ASPR: 12,082.06/100,000), with 214.6 million incident cases (ASIR: 4,916.68/100,000) and 4.1 million YLDs (ASYR: 94.47/100,000).ConclusionGERD poses a growing global health challenge. Insights from these observed epidemiological patterns can assist policymakers in developing targeted measures to reduce its impact, particularly in high-risk regions and younger demographics.